Asymptotic solutions of transient waves generated by a wavemaker in water of uniform depth - Haiqi Fang; Peter H.-Y. Lo; Pengzhi Lin; Philip L.-F. Liu (Wave Motion, 2027)

Magmatic evolution characteristics and heterogeneity of the outer zone of the Emeishan Large Igneous Province: a case study of basalts from the Tianquan and Huayingshan areas - C. C. Li; S. Yang; Z. Y. Lin; Y. P. Jing; Y. Xia; Y. H. Chen; J. T. Liao; C. D. Nie (Australian Journal of Earth Sciences, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Correction: The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Fered-Fenton enhanced boron-doped diamond electrochemical oxidation for wastewater treatment: Antibiotic degradation, kinetics, and environmental effects - C. Chokejaroenrat; K. Poomipuen; K. Techauay; P. Weaoseng; U. Jermnak; H. Chokthaweepanich; N. Suriyachai; Y.-T. Lin; K. Imsilp; C. Sakulthaew (Journal of Water Process Engineering, 2025)

Landsat 8 OLI atmospheric correction neural network for inland waters in tropical regions - M. Van Nguyen; O. T. La; H. T. T. Nguyen; D. Heriza; B.-Y. Lin; G. Y. I. Ryadi; Chao-Hung Lin; Vinh Quang Pham (International Journal of Environmental Science and Technology, 2025)

Analysis of Increased False-Positive ELISA Results for HIV in the Blood of Donors Infected with SARS-CoV-2 - H. Lin; Z. Wang; Q. Ren; Z. Cai; F. Ge; W. Yuan; T. Liao; Y. Wu; R. Peng; Y. Gu; Y. Kuang (Bulletin of Experimental Biology and Medicine, 2025)

Downregulation of A20 Expression Related to T Cells by Staphylococcal Enterotoxin A Treatment - X. Chen; Y. Yan; C. Lin; J. Yang; H. Qiu (Bulletin of Experimental Biology and Medicine, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

The Palomar twilight survey of ‘Ayló’chaxnim, Atiras, and comets - B.T. Bolin; F.J. Masci; M.W. Coughlin; D.A. Duev; Ž. Ivezić; R.L. Jones; P. Yoachim; T. Ahumada; V. Bhalerao; H. Choudhary; C. Contreras; Y.-C. Cheng; et al. (Icarus, 2025)

Recovery of terephthalic acid from alkali-decrement wastewater by zinc salt-based coagulation - H. Zhu; C. Guo; C. Xu; Y. He; M. Huang; G. Zhou; Y. Lin (International Journal of Environmental Science and Technology, 2025)

Construction and Behavioral Comparison of Two Mouse Models of Cerebral Palsy - Y. Tang; Y. Li; S. Lin; W. Wei; H. Chen (Bulletin of Experimental Biology and Medicine, 2024)

Fluid inclusion characteristics and mechanisms of tin mineralisation in the Jialong tin polymetallic deposits, Jiuwandashan–Yuanbaoshan, northern Guangxi, China - C-L. Meng; L-A. Bai; Z-H. Yue; S-Y. Zhou; Y. Dai; Z-H. Feng; X-J. Liu; H. Zhang; L-Z. Lin (Australian Journal of Earth Sciences, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Protective Effect of Protocatechuic Aldehyde on Cerebral Ischemia/Reperfusion Injury in Rats through Blood—Brain Barrier Protection - F. He; J. Feng; H. Sun; Y. Xu; H. Yan; X. Song; Y. Wang; X. Li; Q. Lin (Bulletin of Experimental Biology and Medicine, 2024)

P21-52 Paraquat disrupts KIF5A-mediated axonal mitochondrial transport in midbrain neurons and its antagonism by melatonin - H. Hong; J. Li; T. Tong; X. Lin; Y. Xu; J. Lin; S. Liu; K. Luo; Z. Zhou (Toxicology Letters, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Identification of pollution sources in rivers by downstream analysis of low-concentration elements associated with wastewater - H.-C. Lin; P.-Y. Hsieh; G.-S. Wang; D.-W. Wang; T.-H. Wang; Y.-C. Hsu; C.-F. Wu (International Journal of Environmental Science and Technology, 2024)

Critical roles of tubular mitochondrial ATP synthase dysfunction in maleic acid-induced acute kidney injury - Hugo Y.-H. Lin; Chan-Jung Liang; Ming-Yu Yang; Phang-Lang Chen; Tzu-Ming Wang; Yen-Hua Chen; Yao-Hsiang Shih; Wangta Liu; Chien-Chih Chiu; Chih-Kang Chiang; Chang-Shen Lin; Han-Chen Lin (Apoptosis, 2024)
Maleic acid (MA) induces renal tubular cell dysfunction directed to acute kidney injury (AKI). AKI is an increasing global health burden due to its association with mortality and morbidity. However, targeted therapy for AKI is lacking. Previously, we determined mitochondrial-associated proteins are MA-induced AKI affinity proteins. We hypothesized that mitochondrial dysfunction in tubular epithelial cells plays a critical role in AKI. In vivo and in vitro systems have been used to test this hypothesis. For the in vivo model, C57BL/6 mice were intraperitoneally injected with 400 mg/kg body weight MA. For the in vitro model, HK-2 human proximal tubular epithelial cells were treated with 2 mM or 5 mM MA for 24 h. AKI can be induced by administration of MA. In the mice injected with MA, the levels of blood urea nitrogen (BUN) and creatinine in the sera were significantly increased ( p p p p p p

Biocontrol of strawberry Botrytis gray mold and prolong the fruit shelf-life by fumigant Trichoderma spp. - Q. S. Fan; H. J. Lin; Y. J. Hu; J. Jin; H. H. Yan; R. Q. Zhang (Biotechnology Letters, 2024)

Dynamic efficiency evaluation of electric power and environmental treatment efficiency in China - Y. Li; Y. Chiu; T.-Y. Lin; S.-M. Wang; T.-H. Chang (International Journal of Environmental Science and Technology, 2024)

Synthesis of nano-MgO hybrid SDB hydrophobic catalyst carriers and its adsorption behavior of Fe3+ - Y. Fan; H. R. Peng; C. Li; K. Fu; X. Y. Ren; H. J. Yang; S. D. Lin; C. L. Liu (International Journal of Environmental Science and Technology, 2024)

The effect of polychlorinated biphenyls extracted from offshore sediments on the intestinal epithelium and microflora of zebrafish - M. Zhang; D-H Zhu; Q-L Song; M-M Chen; Y Hu; D-J Kang; Z-B Chen; H-Y Lin; F-H Nie; J-J Chen (International Journal of Environmental Science and Technology, 2023)

Characterization of fouled ultrafiltration membranes from a full-scale wastewater reclamation plant in iron and steel industry - P.-H. Lin; Y.-C. Su; C.-L. Chen; I.-Y. Tsao (International Journal of Environmental Science and Technology, 2023)

The impact of education level on residents’ carbon consumption in China - Y.-N. Lin; Y.-H. Chiu; T.-H. Chang; T.-Y. Lin; S.-Y. Chiu (International Journal of Environmental Science and Technology, 2023)

Geological controls on the distribution of gas hydrates in the shallow parts of the gas hydrate stability zone – constraints from seafloor drilling off Taiwan - G. Bohrmann; C. Berndt; S. Lin; T.-H. Tu; A.T. Lin; H.-H. Hsu; M.-C. Lai; W.-C. Chi; C. Deusner; J. Elger; K. Wallmann; T. Freudenthal; et al. (Marine and Petroleum Geology, 2023)

Virulence assessment of four Glaesserella parasuis strains isolated in Liaoning province of China - Ping Yan; Yong C. Jia; Xue L. Zhang; Yuan Y. Zhou; Ying Guo; Rong L. Yin; Jing Yuan; Lin X. Wang; Zhong B. Guo; Jing Y. Wang; Xin Wang; Rong H. Yin (Research in Veterinary Science, 2023)

Characterizing breast cancer incidence and trends among Asian American, Native Hawaiian, and non-Hispanic White women in Hawaiʻi, 1990-2014 - Ugonna Ihenacho; Meg A. McKinley; Annie Vu; Brenda Y. Hernandez; Lenora W. M. Loo; Scarlett Lin Gomez; Anna H. Wu; Iona Cheng (Cancer Causes & Control, 2023)

Effects of pre-oxidation by ozone, permanganate and ferrate on generation and toxicities of disinfection byproducts - Y. Lin; Y. Lou; A. Li; Y. Wei; H. Li; M. Zhou; Y. Li (International Journal of Environmental Science and Technology, 2022)

A bibliometric review of peripartum cardiomyopathy compared to other cardiomyopathies using artificial intelligence and machine learning - M. Grosser; H. Lin; M. Wu; Y. Zhang; S. Tipper; D. Venter; J. Lu; C. G. dos Remedios (Biophysical Reviews, 2022)

Determining tolerance levels for quality assurance of 3D printed bolus for modulated arc radiotherapy of the nose - T. Kairn; S. Talkhani; P. H. Charles; B. Chua; C. Y. Lin; A. G. Livingstone; S. K. Maxwell; T. Poroa; E. Simpson-Page; E. Spelleken; M. Vo; S. B. Crowe (Physical and Engineering Sciences in Medicine, 2021)

Petrological and isotopic data from Eocene granites in the Luocang area, South Lhasa terrane, Tibet: implications for the India–Eurasia collision - J.-G. Gao; F. Ding; J.-Q. Lin; Q.-H. Zhu; Y. Sun; X.-G. Xie (Australian Journal of Earth Sciences, 2021)

A drug-tunable Flt23k gene therapy for controlled intervention in retinal neovascularization - Jinying Chen; Fan-Li Lin; Jacqueline Y. K. Leung; Leilei Tu; Jiang-Hui Wang; Yu-Fan Chuang; Fan Li; Hsin-Hui Shen; Gregory J. Dusting; Vickie H. Y. Wong; Leszek Lisowski; Alex W. Hewitt; et al. (Angiogenesis, 2021)

Suitable plant combinations for ecological floating beds in eutrophic subtropical coastal wetlands under different salinities: experimental evidences - J. C. Lyu; G. H. Lin; Z. Y. Fan; W. X. Lin; Z. Dai (International Journal of Environmental Science and Technology, 2020)

A Major Hydrothermal Reservoir Underneath the Tatun Volcano Group of Taiwan: Clues from a Dense Linear Geophone Array - C. H. Lin; Y. C. Lai; M. H. Shih; C. J. Lin; J. S. Ku; Y. C. Huang (Pure and Applied Geophysics, 2020)
A dense linear geophone array is deployed across the Tatun volcano group (TVG) at the northern tip of Taiwan, where more than 7 million residents live in the Taipei metropolis. The array is composed of 50 geophones with a station spacing of ~ 200 m in average, and it is designed for striking in the NW–SE direction to record the many earthquakes in eastern Taiwan, where the Philippine Sea plate subducted beneath the Eurasia plate. The detailed examination of felt earthquakes shows consistent P-wave delays are recorded at particular stations of the array. The further forward modeling indicates there is a low-velocity zone (LVZ) at depths between ~ 0.5 and ~ 2.5 km beneath the major fumarole sites. Combining this preliminary result with previous studies including clustering seismicity, volcanic earthquakes, low-resistivity zone, strong degassing processes and shallow velocity structures, we suggest that the LVZ might be associated with the major hydrothermal reservoir at the TVG. The identification of the hydrothermal reservoir by the LVZ not only implies a potential volcanic threat, such as phreatic eruptions, in the future, but also provides the possibility of sustainable geothermal resources for replacing traditional nuclear and fossil fuel power plants. Detailed images of the LVZ and other volcanic structures will be obtained soon when dense geophone arrays with more than 600 geophones are deployed from 2020 to 2022.

Managing water quality in a river basin with uncertainty - H.-W. Chen; W.-Y. Chen; C.-T. Wang; Y.-H. Lin; M.-J. Deng; C.-Y. Chiang (International Journal of Environmental Science and Technology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Noise exposure assessment and prevention around high-speed rail - K.-T. Tsai; M.-D. Lin; Y.-H. Lin (International Journal of Environmental Science and Technology, 2019)

Seasonal climatic effects and feedbacks of anthropogenic heat release due to global energy consumption with CAM5 - Bing Chen; C. Wu; X. Liu; L. Chen; Jian Wu; H. Yang; Tao Luo; Xue Wu; Yiquan Jiang; Lei Jiang; H. Y. Brown; Z. Lu; et al. (Climate Dynamics, 2019)

Cr-induced disturbance on expression of six COX genes in rice seedlings - X.-Z. Yu; C.-J. Lu; Y.-J. Lin; Y.-H. Li (International Journal of Environmental Science and Technology, 2019)

Carbon steel slag and stainless steel slag for removal of arsenic from stimulant and real groundwater - W. Shi; H. Li; G. Liao; G. Pei; Y. Lin (International Journal of Environmental Science and Technology, 2018)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

DNA Barcoding for Identification of Sugarcane Borers in China - J- D Wang; W- Z Wang; Z- L Lin; A Ali; H- Y Fu; M- T Huang; S- J Gao; R Wang (Neotropical Entomology, 2018)

Comparison of endosperm amyloplast development and degradation in waxy and non-waxy wheat - H. Yu; Y. Yang; X.Y. Chen; G.X. Lin; J.Y. Sheng; J.Y. Nie; Q.J. Wang; E.J. Zhang; X.R. Yu; Z. Wang; F. Xiong (Cereal Research Communications, 2018)

Rice ecosystem services in South-east Asia - Josef Settele; Kong Luen Heong; Ingolf Kühn; Stefan Klotz; Joachim H. Spangenberg; Gertrudo Arida; Alexis Beaurepaire; Silke Beck; Erwin Bergmeier; Benjamin Burkhard; Roland Brandl; Jesus Victor Bustamante; et al. (Paddy and Water Environment, 2018)

Glucohexaose-induced protein phosphatase 2C regulates cell redox status of cucumber seedling - Q M Chen; Y Yu; C M Lin; N Cui; J Y Zhao; T F Song; H Y Fan (Journal of Biosciences, 2018)

Temporal changes in soil C‐N‐P stoichiometry over the past 60 years across subtropical China - Zaipeng Yu; Minhuang Wang; Zhiqun Huang; Teng‐Chiu Lin; Matthew A. Vadeboncoeur; Eric B. Searle; Han Y. H. Chen (Global Change Biology, 2018)
Controlled experiments have shown that global changes decouple the biogeochemical cycles of carbon (C), nitrogen (N), and phosphorus (P), resulting in shifting stoichiometry that lies at the core of ecosystem functioning. However, the response of soil stoichiometry to global changes in natural ecosystems with different soil depths, vegetation types, and climate gradients remains poorly understood. Based on 2,736 observations along soil profiles of 0–150 cm depth from 1955 to 2016, we evaluated the temporal changes in soil C‐N‐P stoichiometry across subtropical China, where soils are P‐impoverished, with diverse vegetation, soil, and parent material types and a wide range of climate gradients. We found a significant overall increase in soil total C concentration and a decrease in soil total P concentration, resulting in increasing soil C:P and N:P ratios during the past 60 years across all soil depths. Although average soil N concentration did not change, soil C:N increased in topsoil while decreasing in deeper soil. The temporal trends in soil C‐N‐P stoichiometry differed among vegetation, soil, parent material types, and spatial climate variations, with significantly increased C:P and N:P ratios for evergreen broadleaf forest and highly weathered Ultisols, and more pronounced temporal changes in soil C:N, N:P, and C:P ratios at low elevations. Our sensitivity analysis suggests that the temporal changes in soil stoichiometry resulted from elevated N deposition, rising atmospheric CO 2 concentration and regional warming. Our findings revealed that the responses of soil C‐N‐P and stoichiometry to long‐term global changes have occurred across the whole soil depth in subtropical China and the magnitudes of the changes in soil stoichiometry are dependent on vegetation types, soil types, and spatial climate variations.

Molecular screening of multidrug-resistance tuberculosis by a designated public health laboratory in Taiwan - H.-C. Lin; C.-L. Perng; Y.-W. Lai; F.-G. Lin; C.-J. Chiang; H.-A. Lin; R. Jou; T.-S. Chiueh (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

The Quantitative Structural and Compositional Analyses of Degenerating Intervertebral Discs Using Magnetic Resonance Imaging and Contrast-Enhanced Micro-Computed Tomography - Kevin H. Lin; Simon Y. Tang (Annals of Biomedical Engineering, 2017)

Helicobacter pylori infection increases the risk of adult-onset asthma: a nationwide cohort study - Y-C Wang; T-Y Lin; S-T Shang; H-J Chen; C-H Kao; C-C Wu; T-Y Yang (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Experimental Investigation of the Anisotropic Mechanical Properties of a Columnar Jointed Rock Mass: Observations from Laboratory-Based Physical Modelling - H. Ji; J. C. Zhang; W. Y. Xu; R. B. Wang; H. L. Wang; L. Yan; Z. N. Lin (Rock Mechanics and Rock Engineering, 2017)

Gonorrhea infection increases the risk of prostate cancer in Asian population: a nationwide population-based cohort study - Y.-C. Wang; C.-H. Chung; J.-H. Chen; M.-H. Chiang; Ti-Yin; C.-H. Tsao; F.-H. Lin; W.-C. Chien; S.-T. Shang; F.-Y. Chang (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Identification of diverse bacterial communities for potential bio-aids capable of troubleshooting for wastewater biological treatment processes - H-W Kuo; C-Y Huang; C-N Chang; P-L Lee; Y-W Chen; C-F Huang; H-H Chang; Y-H Tang; S-Z Zeng; G-Y Li; C-R Lin; L-Z Chen (International Journal of Environmental Science and Technology, 2017)

Variability of hydrological extreme events in East Asia and their dynamical control: a comparison between observations and two high-resolution global climate models - N. Freychet; A. Duchez; C.-H. Wu; C.-A. Chen; H.-H. Hsu; J. Hirschi; A. Forryan; B. Sinha; A. L. New; T. Graham; M. B. Andrews; C.-Y. Tu; et al. (Climate Dynamics, 2017)

Structuraland antigenic analysis of a new Rhoptry Pseudokinase Gene (ROP54) in Toxoplasma gondii - Jian Zhou; Gang Lu; Lin Wang; Aihua H. Zhou; Yali L. Han; Jingjing J. Guo; Pengxia X. Song; Huaiyu Y. Zhou; Hua Cong; Ming Hou; Shenyi Y. He (Acta Parasitologica, 2017)
is defined as an obligate intracellular apicomplexan parasite and influences approximatelyone-third of the human all over the world. ROP54 protein is expressed in the rhoptry of

A new region-based preparatory factor for landslide susceptibility models: the total flux - C. C. Liu; W. Luo; M. C. Chen; Y. T. Lin; H. L. Wen (Landslides, 2016)

Early detection of Mycobacterium tuberculosis complex in BACTEC MGIT cultures using nucleic acid amplification - S. Y. Lin; S. C. Hwang; Y. C. Yang; C. F. Wang; Y. H. Chen; T. C. Chen; P. L. Lu (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Epidemiology and characteristics of the dengue outbreak in Guangdong, Southern China, in 2014 - L. Huang; X. Luo; J. Shao; H. Yan; Y. Qiu; P. Ke; W. Zheng; B. Xu; W. Li; D. Sun; D. Cao; C. Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

The impact of global budgeting on health service utilization, health care expenditures, and quality of care among patients with pneumonia in Taiwan - C.-Y. Lin; T. Ma; C.-C. Lin; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Drought tolerance as a driver of tropical forest assembly: resolving spatial signatures for multiple processes - M. K. Bartlett; Y. Zhang; J. Yang; N. Kreidler; S.‐W. Sun; L. Lin; Y.‐H. Hu; K.‐F. Cao; L. Sack (Ecology, 2016)
Spatial patterns in trait variation reflect underlying community assembly processes, allowing us to test hypotheses about their trait and environmental drivers by identifying the strongest correlates of characteristic spatial patterns. For 43 evergreen tree species (>1 cm dbh) in a 20‐ha seasonal tropical rainforest plot in Xishuangbanna, China, we compared the ability of drought‐tolerance traits, other physiological traits, and commonly measured functional traits to predict the spatial patterns expected from the assembly processes of habitat associations, niche‐overlap‐based competition, and hierarchical competition. We distinguished the neighborhood‐scale (0–20 m) patterns expected from competition from larger‐scale habitat associations with a wavelet method. Species’ drought tolerance and habitat variables related to soil water supply were strong drivers of habitat associations, and drought tolerance showed a significant spatial signal for influencing competition. Overall, the traits most strongly associated with habitat, as quantified using multivariate models, were leaf density, leaf turgor loss point (π tlp ; also known as the leaf wilting point), and stem hydraulic conductivity ( r 2 range for the best fit models = 0.27–0.36). At neighborhood scales, species spatial associations were positively correlated with similarity in π tlp , consistent with predictions for hierarchical competition. Although the correlation between π tlp and interspecific spatial associations was weak ( r 2

Histological analysis of somatic embryogenesis in pineapple: AcSERK1 and its expression validation under stress conditions - J. Ma; Y. H. He; Z. Y. Hu; S. Kanakala; W. T. Xu; J. X. Xia; C. H. Guo; S. Q. Lin; C. J. Chen; C. H. Wu; J. L. Zhang (Journal of Plant Biochemistry and Biotechnology, 2016)

Biodegradation of atrazine by Arthrobacter sp. C3, isolated from the herbicide-contaminated corn field - H. Wang; Y. Liu; J. Li; M. Lin; X. Hu (International Journal of Environmental Science and Technology, 2016)

Melatonin Ameliorates Arsenite-Induced Neurotoxicity: Involvement of Autophagy and Mitochondria - Y. C. Teng; Y. I. Tai; H. J. Huang; A. M. Y. Lin (Molecular Neurobiology, 2015)

Diversity and degradation mechanism of an anaerobic bacterial community treating phenolic wastewater with sulfate as an electron acceptor - X. J. Guo; Z. Y. Lu; P. Wang; H. Li; Z. Z. Huang; K. F. Lin; Y. D. Liu (Environmental Science and Pollution Research, 2015)

Neurology of the H1N1 pandemic in Singapore: a nationwide case series of children and adults - Asha Prerna; Jocelyn Y. X. Lim; Natalie W. H. Tan; Mas Suhaila Isa; Helen May-Lin Oh; Norazieda Yassin; Chian-Yong Low; Derrick W. S. Chan; Chia-Yin Chong; Yee-Sin Leo; Angela Li-Ping Chow; Paul Ananth Tambyah; et al. (Journal of NeuroVirology, 2015)

Identification and characterization of a late gene encoded by grouper iridovirus 2L (GIV‐2L) - H‐Y Lin; C‐F Cheng; P P Chiou; C‐J Liou; J‐C Yiu; Y‐S Lai (Journal of Fish Diseases, 2015)
Grouper iridovirus (GIV) belongs to the Ranavirus genus and is one of the most important viral pathogens in grouper, particularly at the fry and fingerling stages. In this study, we identified and characterized the GIV‐2L gene, which encodes a protein of unknown function. GIV‐2L is 1242 bp in length, with a predicted protein mass of 46.2 kDa. It displayed significant identity only with members of the Ranavirus and Iridovirus genera. We produced mouse monoclonal antibodies against the GIV‐2L protein by immunizing mice with GIV‐2L‐His‐tag recombinant protein. By inhibiting de novo protein and DNA synthesis in GIV‐infected cells, we showed that GIV‐2L was a late gene during the viral replication. Finally, immunofluorescence microscopy revealed that GIV‐2L protein accumulated in both the nucleus and cytoplasm of infected cells. These results offer important insights into the pathogenesis of GIV.

Ambient air concentrations of PCDD/Fs, coplanar PCBs, PBDD/Fs, and PBDEs and their impacts on vegetation and soil - Y.-C. Kuo; Y.-C. Chen; M.-Y. Lin; L.-H. Young; H.-T. Hsu; S.-H. Liou; T.-N. Wu; L.-C. Wang; P.-J. Tsai (International Journal of Environmental Science and Technology, 2015)

Neonatal urinary tract infection may increase the risk of childhood asthma - C.-H. Lin; Y.-C. Wang; W.-C. Lin; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

The application of the cluster identification method for the detection of leakages in water distribution networks - H.-Y. Lin; B.-W. Lin; P.-H. Li; J.-J. Kao (International Journal of Environmental Science and Technology, 2015)

Statins can increase the risk of herpes zoster infection in Asia - H.-H. Chen; C.-L. Lin; C.-J. Yeh; S.-Y. Yeh; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Balanitis is a risk factor for herpes zoster - C.-Y. Hsu; C.-L. Lin; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Mass mortality associated with a viral‐induced anaemia in cage‐reared large yellow croaker, Larimichthys crocea (Richardson) - W J Xu; Z D Qin; H Shi; N Jiang; Y Zhou; X L Liu; J J Xie; G S Wang; W M Wang; M Asim; L B Zeng; L Lin (Journal of Fish Diseases, 2015)

Anti-tuberculosis treatments and risk of hepatocellular carcinoma in tuberculosis patients with liver cirrhosis: a population-based case–control study - Y.-P. Lim; C.-L. Lin; D.-Z. Hung; Y.-N. Lin; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

ICE1 demethylation drives the range expansion of a plant invader through cold tolerance divergence - H. J. Xie; H. Li; D. Liu; W. M. Dai; J. Y. He; S. Lin; H. Duan; L. L. Liu; S. G. Chen; X. L. Song; B. E. Valverde; S. Qiang (Molecular Ecology, 2015)
Cold tolerance adaption is a crucial determinant for the establishment and expansion of invasive alien plants into new cold environments; however, its evolutionary mechanism is poorly understood. Crofton weed ( Ageratina adenophora ), a highly invasive alien plant, is continuously spreading across subtropical areas in China, north‐eastward from the first colonized south‐western tropical regions, through cold tolerance evolution. Close relations between the cold tolerance levels of 34 populations, represented by 147 accessions, and the latitude, extreme lowest temperature, coldest month average temperature, and invasion period have provided direct insight into its cold tolerance divergence. A comparative study of the CBF pathway, associated with the cold tolerance enhancement of cold‐susceptible CBF 1 ‐transgenic plant, among four geographically distinct crofton weed populations revealed that the CBF pathway plays a key role in the observed cold tolerance divergence. Four epialleles of the cold response regulator ICE 1 ranged from 66 to 50 methylated cytosines, representing a 4.4% to 3.3% methylation rate and significantly corresponding to the lowest to highest cold tolerance levels among these different populations. The significant negative relation between the transcription levels of the primary CBF pathway members, except for CBF 2 , and the methylation levels among the four populations firstly demonstrates that the demethylation‐upregulated transcription level of CBF pathway is responsible for this evolution. These facts, combined with the cold tolerance variation and methylation found among three native and two other introduced populations, indicate that the ICE 1‐ demethylated upregulation of cold tolerance may be the underlying evolutionary mechanism allowing crofton weed to expand northward in China.

Helicobacter pylori infection and the risk of acute coronary syndrome: a nationwide retrospective cohort study - C.-Y. Lai; T.-Y. Yang; C.-L. Lin; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

The complex interplay among bacterial motility and virulence factors in different Escherichia coli infections - C. Y. Kao; W. H. Lin; C. C. Tseng; A. B. Wu; M. C. Wang; J. J. Wu (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Trends in the susceptibility of commonly encountered clinically significant anaerobes and susceptibilities of blood isolates of anaerobes to 16 antimicrobial agents, including fidaxomicin and rifaximin, 2008–2012, northern Taiwan - F. D. Wang; C. H. Liao; Y. T. Lin; W. H. Sheng; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Effect of nano-hematite morphology on photocatalytic activity - Y. H. Chen; C. C. Lin (Physics and Chemistry of Minerals, 2014)

The first record, tagging and release of a neonatal whale shark Rhincodon typus in Taiwan - H. H. Hsu; C. Y. Lin; S. J. Joung (Journal of Fish Biology, 2014)
On 27 October 2013, a Rhincodon typus was apparently chased by a group of Caranx ignobilis into nearshore waters near Green Island (Ludao), east of Taiwan. A fisherman brought it back to port where it was kept in a small sea pen until release. The R. typus was 78 cm total length, and was tagged and released on 29 October 2013.

Comparison of interpolation methods for estimating spatial distribution of precipitation in Ontario, Canada - S. Wang; G. H. Huang; Q. G. Lin; Z. Li; H. Zhang; Y. R. Fan (International Journal of Climatology, 2014)
In this study, different interpolation techniques in a geographical information system ( GIS ) environment are analysed and compared for estimating the spatial distribution of precipitation in the province of Ontario, Canada. A high‐resolution regional climate modelling system [Providing Regional Climates for Impacts Studies ( PRECIS )] is used to simulate the present (1961–1990) and future (2071–2100) precipitation events for 12 meteorological stations over Ontario. The results verify that for the present case PRECIS simulates well the precipitation events when compared with observed data. The future precipitation events can be projected after the validation of PRECIS . Six interpolation methods are then used to generate spatial distribution of precipitation based on the projections of future precipitation of 12 meteorological stations; they include inverse distance weighting ( IDW ), global polynomial interpolation ( GPI ), local polynomial interpolation ( LPI ), radial basis functions ( RBF ), ordinary kriging ( OK ), and universal kriging ( UK ). Cross‐validation is applied to evaluate the accuracy of interpolation methods in terms of the root mean square error ( RMSE ). The results indicate that LPI is the optimal method with the least RMSE for interpolating the PRECIS precipitation. LPI is then used to analyse spatial variations of the average annual precipitation for the period of 2071–2100 over Ontario.

Modeling chromium(VI) reduction by Escherichia coli 33456 using ceramic pearl as a supporting medium - Y.-H. Lin (International Journal of Environmental Science and Technology, 2014)

Association between herpes zoster and end stage renal disease entrance in chronic kidney disease patients: a population-based cohort study - S.-Y. Lin; J.-H. Liu; H.-C. Yeh; C.-L. Lin; I.-J. Tsai; P.-C. Chen; F.-C. Sung; Y.-F. Yang; C.-C. Huang; D. E. Morisky; Y.-J. Chang; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

On the origin of water-soluble organic tracer compounds in fine aerosols in two cities: the case of Los Angeles and Barcelona - M. Alier; M. Dall Osto; Y.-H. Lin; J. D. Surratt; R. Tauler; J. O. Grimalt; B. L. van Drooge (Environmental Science and Pollution Research, 2014)

Convergent transcription through microsatellite repeat tracts induces cell death - William Y. Lin; Yunfu Lin; John H. Wilson (Molecular Biology Reports, 2014)

The association between chronic osteomyelitis and increased risk of diabetes mellitus: a population-based cohort study - S.-Y. Lin; C.-L. Lin; C.-H. Tseng; I.-K. Wang; S.-M. Wang; C.-C. Huang; Y.-J. Chang; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Erratum to: Increased risk of chronic fatigue syndrome following herpes zoster: a population-based study - S.-Y. Tsai; T.-Y. Yang; H.-J. Chen; C.-S. Chen; W.-M. Lin; W.-C. Shen; C.-N. Kuo; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Clinical and microbiological characteristics of Klebsiella pneumoniae from community-acquired recurrent urinary tract infections - W. H. Lin; C. Y. Kao; D. C. Yang; C. C. Tseng; A. B. Wu; C. H. Teng; M. C. Wang; J. J. Wu (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Increased risk of chronic fatigue syndrome following herpes zoster: a population-based study - S.-Y. Tsai; T.-Y. Yang; H.-J. Chen; C.-S. Chen; W.-M. Lin; W.-C. Shen; C.-N. Kuo; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Evaluation of seedling resistance of rice germplasm resources to sheath blight (Rhizoctonia solani) - B. Chen; L.-W. Li; Y.-J. Lin; Z.-H. Wang; G.-D. Lu (Cereal Research Communications, 2014)

Molecular characterization of domestic and exotic potato virus S isolates and a global analysis of genomic sequences - Y.-H. Lin; J. A. Abad; C. J. Maroon-Lango; K. L. Perry; H. R. Pappu (Archives of Virology, 2014)

Characterization, tissue distribution and regulation of neuropeptideY in Schizothorax prenanti - R. Wei; C. Zhou; D. Yuan; T. Wang; F. Lin; H. Chen; H. Wu; Z. Xin; S. Yang; Y. Wang; D. Chen; J. Liu; et al. (Journal of Fish Biology, 2014)
In this study, the full‐length neuropeptide Y ( npy ) complementary (c) DNA was cloned in ya fish Schizothorax prenanti . npy cDNA was composed of 789 nucleotides with a 288 nucleotide open reading frame encoding a protein of 96 amino acids. The deduced amino acid sequences contained a 28 amino acids signal peptide followed by a 36 amino acids mature neuropeptide Y (NPY). The npy mRNA was expressed mainly in the brain and eye as detected by real‐time quantitative polymerase chain reaction RT‐PCR ( rt‐qPCR ). The S. prenanti NPY was detectable from blastulation to hatch, suggesting that npy might be involved in the late embryonic development of S. prenanti . An experiment was conducted to determine the expression profile of npy during feeding of a single meal and during long‐term fasting. The expression level of npy in fed fish was significantly decreased at 0·5, 1·5, 3 and 9 h post‐feeding (hpf) than in fasting fish. Fasting for 14 days induced an increase in npy messenger (m) RNA expression in the brain. Overall, the results suggest that NPY is a conserved peptide that might be involved in the regulation of feeding and other physiological function in S. prenanti .

Characterization of Schizothorax prenanti cgnrhII gene: fasting affects cgnrhII expression - T. Wang; D. Yuan; C. Zhou; F. Lin; H. Chen; H. Wu; R. Wei; Z. Xin; J. Liu; Y. Gao; D. Chen; S. Yang; et al. (Journal of Fish Biology, 2014)
In this study, the role of chicken gonadotropin‐releasing hormone II ( cgnrhII ) in feeding regulation was investigated in Schizothorax prenanti . First, the full‐length S. prenanti cgnrhII cDNA consisted of 693 bp with an open reading frame of 261 bp encoding a protein of 86 amino acids. Next, cgnrhII was widely expressed in the central and peripheral tissues. Last, there were significant changes in cgnrhII mRNA expression in the fasted group compared to the fed group in the S. prenanti hypothalamus during 24 h fasting ( P cgnrhII gene expression presented a significant decrease in the fasted group compared with the fed group ( P cgnrhII mRNA expression level between refed and fed group on day 9 ( P > 0·05). Thus, the results suggest that cGnRH II expression is influenced by fasting and the gene may be involved in feeding regulation in S. prenanti.

Clinical characteristics and outcomes of patients with pleural infections due to Stenotrophomonas maltophilia at a medical center in Taiwan, 2004–2012 - M.-R. Lee; H.-C. Wang; C.-Y. Yang; C.-K. Lin; H.-Y. Kuo; J.-C. Ko; W.-H. Sheng; L.-N. Lee; C.-J. Yu; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Pressure-assisted cyclic washing of heavy-metal-contaminated sediments - C. E. Lin; P. K. A. Hong; H. Y. Chiu; R. Y. Surampalli; C. T. Lin; C. M. Kao (International Journal of Environmental Science and Technology, 2014)

Association between polymorphisms in the csrRS two-component regulatory system and invasive group A streptococcal infection - J.-N. Lin; L.-L. Chang; C.-H. Lai; H.-H. Lin; Y.-H. Chen (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Trends in the susceptibility of methicillin-resistant Staphylococcus aureus to nine antimicrobial agents, including ceftobiprole, nemonoxacin, and tyrothricin: results from the Tigecycline In Vitro Surveillance in Taiwan (TIST) study, 2006–2010 - Y.-H. Chen; C.-Y. Liu; W.-C. Ko; C.-H. Liao; P.-L. Lu; C.-H. Huang; C.-T. Lu; Y.-C. Chuang; S.-M. Tsao; Y.-S. Chen; Y.-C. Liu; W.-Y. Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Evaluating the protective efficacy of antigen combinations against P hotobacterium damselae ssp. piscicida infections in cobia, Rachycentron canadum L. - L‐P Ho; C‐J Chang; H‐C Liu; H‐L Yang; J H‐Y Lin (Journal of Fish Diseases, 2014)
Cobia, Rachycentron canadum L., is a very important aquatic fish that faces the risk of infection with the bacterial pathogen P hotobacterium damselae ssp. piscicida , and there are few protective approaches available that use multiple antigens. In the present study, potent bivalent antigens from P . damselae ssp. piscicida showed more efficient protection than did single antigens used in isolation. In preparations of three antigens that included recombinant heat shock protein 60 ( rHSP 60), recombinant α‐enolase ( rENOLASE ) and recombinant glyceraldehyde‐3‐phosphate dehydrogenase ( rGAPDH ), we analysed the doses that elicited the best immune responses and found that this occurred at a total of 30 μg of antigen per fish. Subsequently, vaccination of fish with rHSP 60, rENOLASE and rGAPDH achieved 46.9, 52 and 25% relative per cent survival (RPS), respectively. In addition, bivalent subunit vaccines – combination I ( rHSP 60 + rENOLASE ), combination II ( rENOLASE + rGAPDH ) and combination III ( rHSP 60 + rGAPDH ) – were administered and the RPS in these groups (65.6, 64.0 and 48.4%, respectively), was higher than that achieved with single‐antigen administration. Finally, in combination IV , the trivalent vaccine rHSP 60 + rENOLASE + rGAPDH , the RPS was 1.6%. Taken together, our results suggest that combinations of two antigens may achieve a better efficiency than monovalent or trivalent antigens, and this may provide new insights into pathogen prevention strategies.

Role of HO-1 in the Arsenite-Induced Neurotoxicity in Primary Cultured Cortical Neurons - Y. C. Teng; Y. I. Tai; Y. H. Lee; A. M. Y. Lin (Molecular Neurobiology, 2013)

Soluble interleukin‐1 receptor, a potential negative regulator of orange‐spotted grouper Epinephelus coioides interleukin‐1 system - D. Q. Lu; M. Yao; S. B. Yi; Y. W. Li; X. C. Liu; Y. Zhang; H. R. Lin (Journal of Fish Biology, 2013)
In this study, the cDNA sequence encoding interleukin‐1 ( Il ‐1) receptor‐like protein of orange‐spotted grouper Epinephelus coioides was obtained. The newly identified sequence was named soluble type I Il ‐1 receptor ( sIl‐1rI ) owing to its structural composition, which had two Ig‐like domains, lack of transmembrane region and the Toll/interleukin‐1 receptor ( TIR ) domain, similar to the brown rat Rattus norvegicus soluble Il‐1rI . In addition, sequence comparison and phylogenetic analysis indicated that E. coioides sequence had a closer relationship with Il‐1rI than Il‐1rII . Real‐time PCR revealed that sil‐1rI mRNA expression presented a process of decrease, restoration and increase in Cryptocaryon irritans ‐infected E. coioides . The negative correlation between Il ‐1β and sil‐1rI mRNA in C. irritans ‐infected head‐kidney implied the potential negative regulatory role of sil‐1rI in E. coioides Il ‐1 system. The leucocytes incubated with lipopolysaccharide or polyriboinosinic polyribocytidylic acid exhibited different expression profiles of sil‐1rI . Recombinant Il ‐1β ( rIl ‐1β) protein was capable of inducing sil‐1rI mRNA under the concentration of 100 ng ml −1 , suggesting that high dosage or excess Il ‐1β would stimulate the expression of sil‐1rI to maintain the homoeostasis of E. coioides Il ‐1 system. For the first time, the role of teleost Il‐1rI in parasite infection has been identified, and soluble Il‐1r was found in fish.

The use of procalcitonin in the diagnosis of bone and joint infection: a systemic review and meta-analysis - C.-J. Shen; M.-S. Wu; K.-H. Lin; W.-L. Lin; H.-C. Chen; J.-Y. Wu; M. C.-H. Lee; C.-C. Lee (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Characterization of a novel cell line from the caudal fin of koi carp Cyprinus carpio - S.‐L. Lin; Y.‐H. Cheng; C.‐M. Wen; S.‐N. Chen (Journal of Fish Biology, 2013)
A continuous cell line ( KF ‐101) derived from the caudal fin of the koi carp Cyprinus carpio was established and characterized. The KF ‐101 cell line multiplied abundantly in Leibovitz's L‐15 medium containing 10% foetal bovine serum at 25° C, and was subcultured for >90 passages over a period of 3 years. Immunocytochemistry revealed that the KF ‐101 cells contain keratin, junction proteins connexin‐43 and occludin, and ectodermal stem‐cell marker Pax‐6, but not vimentin. Furthermore, the KF ‐101 cells reacted with anti‐human DARPP ‐32 and anti‐human GATA ‐4 antibodies, and the labelling was regulated according to the cell cycle. The labels of the DARPP ‐32 and GATA ‐4 antibodies in the KF ‐101 cells were the suggested phosphatase‐1 inhibitor‐1 and GATA ‐3, respectively. In addition, the KF ‐101 cells were susceptible to koi herpesvirus but were resistant to eel herpesvirus, iridovirus, grouper nodavirus and chum salmon ( Oncorhynchus keta ) virus. The results indicate that the KF ‐101 cells are suitable materials for investigating biological and virological development.

Analysis of carbamazepine serum by differential pulse voltammetry (DPV) and comparison with fluorescence polarization immunoassay (FPIA): an animal study - W. Y. Lin; M. L. Pan; H. Y. Wang; Y. O. Su; P. W. Huang (Medicinal Chemistry Research, 2012)

Development of microsatellite markers in an ungulate mammal, the Formosan serow (Capricornis swinhoei) - Y. Y. Chang; M. C. Chao; S. T. Ding; E.-C. Lin; H. S. Tsao; H. W. Yuan; P. H. Wang (Conservation Genetics Resources, 2012)

Characterization of carbapenem-nonsusceptible Klebsiella pneumoniae bloodstream isolates at a Taiwanese hospital: clinical impacts of lowered breakpoints for carbapenems - N. Y. Lee; J. J. Wu; S. H. Lin; W. C. Ko; L. H. Tsai; J. J. Yan (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Development of a fluorescent-intercalating-dye-based reverse transcription loop-mediated isothermal amplification assay for rapid detection of seasonal Japanese B encephalitis outbreaks in pigs - C. J. Tian; Z. X. Lin; X. M. He; Q. Luo; C. B. Luo; H. Q. Yu; R. Chen; X. W. Wu; D. Z. Zhu; Z. J. Ren; Y. Z. Bi; J. Ji (Archives of Virology, 2012)

Regional variation in otolith Sr:Ca ratios of African longfinned eel Anguilla mossambica and mottled eel Anguilla marmorata : a challenge to the classic tool for reconstructing migratory histories of fishes - Y.‐J. Lin; B. M. Jessop; O. L. F. Weyl; Y. Iizuka; S.‐H. Lin; W.‐N. Tzeng; C.‐L. Sun (Journal of Fish Biology, 2012)
Otolith Sr:Ca ratios of the African longfinned eel Anguilla mossambica and giant mottled eel Anguilla marmorata from nine freshwater sites in four rivers of South Africa were analysed to reconstruct their migratory life histories between freshwater and saltwater habitats. For A. mossambica , the Sr:Ca ratios in the otolith edge differed significantly among rivers and had large effect sizes, but did not differ among sites within a river. Otolith Sr:Ca ratios did not differ among rivers for A. marmorata . When rivers were pooled, the edge Sr:Ca ratios of A. mossambica were not significantly different from those of A. marmorata . According to the river‐specific critical Sr:Ca ratio distinguishing freshwater from saltwater residence, most A. mossambica and A. marmorata had saltwater habitat experience after settlement in fresh water. This was primarily during their elver stage or early in the yellow eel stage. During the middle and late yellow eel stage, freshwater residency was preferred and only sporadic visits were made to saltwater habitats. The data also suggest that regional variations in otolith Sr:Ca ratios affect the critical Sr:Ca value and are a challenge for the reconstruction of migratory life histories that should be explicitly considered to avoid bias and uncertainty.

Identification and expression analysis of major histocompatibility complex IIB gene in orange‐spotted grouper Epinephelus coioides - D. Q. Lu; S. B. Yi; M. Yao; Y. W. Li; X. C. Liu; Y. Zhang; H. R. Lin (Journal of Fish Biology, 2012)
In this study, complementary DNA (cDNA) and DNA sequences of major histocompatibility complex (MHC) class IIB genes ( mhcIIB ) were cloned from orange‐spotted grouper Epinephelus coioides . The gene structure of E. coioides mhcIIB consists of five exons and four introns, and its deduced amino acid sequence length is 249 amino acids, including a signal peptide, a peptide‐binding region, an IGC1 domain, a transmembrane region and a cytoplasmic tail. A phylogenetic study showed that E. coioides mhcIIB shared 32·0–79·1% identity with those of other teleosts and mammals. Real‐time reverse transcriptase (RT)‐PCR was performed to detect the class IIB gene expression in eight different tissues. To characterize the relationship between E. coioides mhcIIB gene and pathogens, in vivo and in vitro studies were performed. Challenge of Cryptocaryon irritans revealed that class IIB genes were down‐regulated after 24 and 48 h of challenge, and their expression was later restored at 72 h. Stimulation of isolated E. coioides leukocytes with lipopolysaccharide (LPS) and polyinosinic:polycytidylic acid (PolyI:C) significantly increased peripheral blood and spleen mhcIIB expression, while head kidney mhcIIB expression remained constant.

Immunoaffinity chromatography purification and ultra-high-performance liquid chromatography-tandem mass spectrometry determination of four β-agonists in beef - Q.-B. Lin; X.-T. Zhao; H. Song; Y.-L. Pan (Food Additives & Contaminants: Part A, 2012)

Reemerging of enterovirus 71 in Taiwan: the age impact on disease severity - S.-M. Wang; T.-S. Ho; H.-C. Lin; H.-Y. Lei; J.-R. Wang; C.-C. Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

A review of magnetic resonance imaging and diffusion tensor imaging findings in mild traumatic brain injury - M. E. Shenton; H. M. Hamoda; J. S. Schneiderman; S. Bouix; O. Pasternak; Y. Rathi; M.-A. Vu; M. P. Purohit; K. Helmer; I. Koerte; A. P. Lin; C.-F. Westin; et al. (Brain Imaging and Behavior, 2012)

Regional economic impact analysis of earthquakes in northern Taiwan and its implications for disaster reduction policies - H. C. Lin; Y. L. Kuo; D. Shaw; M. C. Chang; T. M. Kao (Natural Hazards, 2012)

Seasonal Variation and Health Risk Assessment of Polycyclic Aromatic Hydrocarbons in Miaoli City, Taiwan - C. C. Wu; T. S. Lin; T. T. Yang; H. W. Hsu; C. L. Chang; C. H. Huang; W. Y. Lin (Bulletin of Environmental Contamination and Toxicology, 2012)

Differential expression profiling of orange‐spotted grouper larvae, Epinephelus coioides (Hamilton), that survived a betanodavirus outbreak - M‐S Wu; C‐W Chen; C‐H Lin; C‐S Tzeng; C‐Y Chang (Journal of Fish Diseases, 2012)
Nervous necrosis virus (NNV), a piscine nodavirus, has caused serious viral nervous necrosis and viral encephalopathy and retinopathy in hatchery‐reared larvae and juveniles of a wide range of marine teleost species worldwide in the last two decades. Although the mortality of NNV‐infected larvae is nearly 100%, there are still some larvae that survive this catastrophe. To comprehensively understand the variations of these survivors at the molecular level, we collected orange‐spotted grouper larvae that survived an NNV outbreak in an indoor hatchery in southern Taiwan to study differential gene expression. Healthy larvae with high, medium and low levels of detected NNV were compared with morbid larvae using a 9600‐clone‐containing grouper larva cDNA microarray, and differential gene expression was further confirmed by a quantitative real‐time polymerase chain reaction. Significant variation exists in healthy larvae. The following genes were upregulated: adenylate kinase 1‐2, myosin binding protein H‐like, myosin light chain 2, myosin light chain 3, tropomyosin, fast/white muscle troponin T embryonic isoform, and parvalbumin 1 and 2 genes. The following genes were downregulated: apolipoprotein A‐I, trypsinogen, pyruvate kinase and astacin‐like metalloprotease. Moreover, immunoglobulin M heavy chain gene transcription was significantly higher in healthy larvae that had high virus levels, indicating that humoral immunity might protect organisms from viral infection. These results suggest that some non‐immune‐related genes may have played important roles in survival during the larval metamorphosis stage, after betanodavirus infection.

Germ cells and fertilization differences among Japanese flounder Paralichthys olivaceus , summer flounder Paralichthys dentatus and their first and second generations - J. Sui; D. Y. Ma; Q. H. Liu; S. H. Xu; Z. Z. Xiao; F. Lin; Y. S. Xiao; J. Li (Journal of Fish Biology, 2012)
The morphology of gametes and the fertilization biology of Japanese flounder Paralichthys olivaceus (Po), summer flounder Paralichthys dentatus (Pd) and their hybrids were examined. Multiple generations (two hybrids: Po♀× Pd♂ (F1) and Pd♀× Po♂; two backcrosses: F1♀× Po♂ and F1♀× Pd♂) were obtained by artificial insemination. Comparison of egg ultrastructure among Po, Pd and F1 showed the morphology of micropyle region and the distribution density of pores were species specific. There were c . 100–200 accessory openings around the micropyle in Po, but not in Pd and F1. The zona radiata thickness and number of parallel bands were similar between F1 and Po, which were different from Pd. Comparison of spermatozoa ultrastructure revealed a close relationship between Po and Pd. Cytologically, the six crosses obeyed normal fertilization and cleavage processes, and only one male pronucleus was observed in a fertilized egg, indicating a monospermic fertilization pattern. Analysis of the time distribution from fertilization to first cleavage revealed an obvious delay at pronucleus fusion in the Pd × Po cross. The delay might indicate some cytoplasmic‐nuclear incompatibility during the process of fertilization.

Biodegradation of Cypermethrin by a newly isolated actinomycetes HU-S-01 from wastewater sludge - Q. S. Lin; S. H. Chen; M. Y. Hu; M. R. Ul Haq; L. Yang; H. Li (International Journal of Environmental Science and Technology, 2011)

Bacteremia caused by Brevundimonas species at a tertiary care hospital in Taiwan, 2000–2010 - M. R. Lee; Y. T. Huang; C. H. Liao; T. Y. Chuang; C. K. Lin; S. W. Lee; C. C. Lai; C. J. Yu; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Assessment of nitrogen contamination of groundwater in paddy and upland fields - Y. H. Kao; C.-W. Liu; C. S. Jang; S. W. Zanh; K. H. Lin (Paddy and Water Environment, 2011)

Migration of silver from nanosilver–polyethylene composite packaging into food simulants - H. Song; B. Li; Q.-B. Lin; H.-J. Wu; Y. Chen (Food Additives & Contaminants: Part A, 2011)

Diagnostic performance of an enzyme-linked immunospot assay for interferon-γ in skeletal tuberculosis - C.-C. Lai; C.-K. Tan; W.-L. Liu; S.-H. Lin; Y.-T. Huang; C.-H. Liao; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Clinical significance of nontuberculous mycobacteria isolates in elderly Taiwanese patients - C.-C. Lai; C. K. Tan; S. H. Lin; W. L. Liu; C. H. Liao; Y. T. Huang; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Seroprevalence of Mycoplasma hyopneumoniae in pigs in subtropical southern China - Y. He; M. J. Xu; D. H. Zhou; F. C. Zou; R. Q. Lin; C. C. Yin; X. H. He; R. Liang; M. Liang; X. Q. Zhu (Tropical Animal Health and Production, 2011)

The detection of “Candidatus Mycoplasma haemobos” in cattle and buffalo in China - Q. L. Su; H. Q. Song; R. Q. Lin; Z. G. Yuan; J. F. Yang; G. H. Zhao; W. Y. Huang; Xing Quan Zhu (Tropical Animal Health and Production, 2010)

Groundwater Assessment at Manukan Island, Sabah: Multidisplinary Approaches - S. M. Praveena; C. Y. Lin; A. Z. Aris; M. H. Abdullah (Natural Resources Research, 2010)

Genetic polymorphisms of the DNA repair geneMPG may be associated with susceptibility to rheumatoid arthritis - S. Y. Chen; L. Wan; C. M. Huang; Y. C. Huang; J. J. C. Sheu; Y. J. Lin; S. P. Liu; Y. C. Lan; C. H. Lai; C. W. Lin; C. H. Tsai; F. J. Tsai (Journal of Applied Genetics, 2010)

Sex-specific genetic architecture of human fatness in Chinese: the SAPPHIRe Study - Y.-F. Chiu; L.-M. Chuang; H.-Y. Kao; K.-C. Shih; M.-W. Lin; W.-J. Lee; T. Quertermous; J. D. Curb; I. Chen; B. L. Rodriguez; C. A. Hsiung (Human Genetics, 2010)

Declining drug resistance of Mycobacterium tuberculosis isolates from elderly patients in Taiwan, 2000–2008 - W.-L. Liu; C.-C. Lai; C.-K. Tan; S.-H. Lin; Y.-T. Huang; C.-H. Liao; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

The chondroprotective effects of ferulic acid on hydrogen peroxide-stimulated chondrocytes: inhibition of hydrogen peroxide-induced pro-inflammatory cytokines and metalloproteinase gene expression at the mRNA level - M. P. Chen; S. H. Yang; C. H. Chou; K. C. Yang; C. C. Wu; Y. H. Cheng; Feng-Huei Lin (Inflammation Research, 2010)

Positive culture for Klebsiella pneumoniae in relevant sputum samples as a predictor of rapidly fatal outcome in septic patients at medical intensive care units - T.-Y. Chuang; C.-J. Lin; T.-C. Chou; H.-H. Huang; S.-W. Lee; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Clinical and genotypic characteristics of extensively drug-resistant and multidrug-resistant tuberculosis - C. C. Lai; C. K. Tan; S. H. Lin; C. H. Liao; Y. T. Huang; C. H. Chou; H. L. Hsu; C. Y. Wang; H. I. Lin; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Comparison of approaches for efficient gene silencing induced by microRNA-based short hairpin RNA and indicator gene expression - Z. X. Shan; Q. X. Lin; C. Y. Deng; Z. L. Zhou; H. H. Tan; Y. H. Fu; X. H. Li; J. N. Zhu; L. P. Mai; S. J. Kuang; S. G. Lin; X. Y. Yu (Molecular Biology Reports, 2010)

Impact of pneumococcal vaccines on invasive pneumococcal disease in Taiwan - W.-H. Liao; S.-H. Lin; C.-C. Lai; C.-K. Tan; C.-H. Liao; Y.-T. Huang; C.-Y. Wang; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

In vitro activities of doripenem and other carbapenems against clinically important bacteria isolated in intensive care units: nationwide data from the SMART Programme - S.-S. Jean; P.-R. Hsueh; W.-S. Lee; H.-T. Chang; M.-Y. Chou; I.-S. Chen; J.-H. Wang; C.-F. Lin; J.-M. Shyr; W.-C. Ko; J.-J. Wu; Y.-C. Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Multiple factors have shaped the phylogeography of Chinese spiny loach Cobitis sinensis in Taiwan as inferred from mitochondrial DNA variation - T.‐Y. Chiang; H.‐D. Lin; K.‐T. Shao; K.‐C. Hsu (Journal of Fish Biology, 2010)
Mitochondrial DNA cytochrome b sequences (1140 bp) in 61 specimens of Chinese spiny loach Cobitis sinensis from 12 drainages in Taiwan were identified as two major clades, exhibiting a southern and a northern distribution, north of TzengWen and south of TzengWen (including TzengWen), respectively. The divergence time between these two phylogroups was estimated at 7·34–9·06 million years before present ( b.p. ), but these two phylogroups were formed c. 3·41–4·23 and 2·22–2·75 M b.p. , respectively. Moreover, geological events have been recalculated that Taiwan Island emerged above sea level at an estimate of c . 4–5 M b.p. , and quickly became its present shape at c. 2 M b.p. through mountain building. These results suggest that these two major clades of C. sinensis in Taiwan might originate from two different continental populations, since the island's initial isolation in the Pliocene. Within southern Taiwan, the initial colonization was hypothesized to be in KaoPing River, followed by its northward dispersal. The high divergence between KaoPing and TzengWen was influenced by glaciations and landforms. Within north Taiwan, the colonization was from the Miaoli Plateau through western Taiwan to north‐eastern and northern Taiwan. This dispersal pattern is concordant with the previously proposed hypothesis. Apparently, both geological and phylogeographic evidence suggested that river capture of the upper Takia River by the LanYang River promoted range expansion in freshwater fishes and also indicated that the Central Range within Taiwan did not act as a barrier to the dispersal of C. sinensis .

Effects of two species of inorganic arsenic on the nutrient physiology of rice seedlings - Hai Bin Wang; H. B. He; G. D. Yang; C. Y. Ye; B. H. Niu; W. X. Lin (Acta Physiologiae Plantarum, 2010)

Artificial neural network analysis for reliability prediction of regional runoff utilization - S. C. Lee; H. T. Lin; T. Y. Yang (Environmental Monitoring and Assessment, 2010)

Seroprevalence of Toxoplasma gondii infection in breeding sows in Western Fujian Province, China - C. Q. Huang; Y. Y. Lin; A. L. Dai; X. H. Li; X. Y. Yang; Z. G. Yuan; X. Q. Zhu (Tropical Animal Health and Production, 2010)

Application and development of a decision-support system for assessing water shortage and allocation with climate change - Tzu-Ming Liu; C. P. Tung; K. Y. Ke; L. H. Chuang; C. Y. Lin (Paddy and Water Environment, 2009)

Genetic variation in colchicine-treated regenerated plants of Eucalyptus globulus Labill. - X. Z. Liu; H. Lin; X. Y. Mo; T. Long; H. Y. Zhang (Journal of Genetics, 2009)

Transpositional activation of mPing in an asymmetric nuclear somatic cell hybrid of rice and Zizania latifolia was accompanied by massive element loss - X. H. Shan; X. F. Ou; Z. L. Liu; Y. Z. Dong; X. Y. Lin; X. W. Li; B. Liu (Theoretical and Applied Genetics, 2009)

Molecular characterization of two potato virus S isolates from late-blight-resistant genotypes of potato (Solanum tuberosum) - Y. H. Lin; K. L. Druffel; J. Whitworth; M. J. Pavek; Hanu R. Pappu (Archives of Virology, 2009)

Identification of three immunodominant regions on leukotoxin protein of Fusobacterium necrophorum - D. B. Sun; R. Wu; G. L. Li; J. S. Zheng; X. P. Liu; Y. C. Lin; D. H. Guo (Veterinary Research Communications, 2009)

Spatio‐temporal variation in the elemental compositions of otoliths of southern bluefin tuna Thunnus maccoyii in the Indian Ocean and its ecological implication - C. H. Wang; Y. T. Lin; J. C. Shiao; C. F. You; W. N. Tzeng (Journal of Fish Biology, 2009)
The elements Na, Mg, Mn, Ca, Sr and Ba in otoliths of southern bluefin tuna Thunnus maccoyii , collected from their feeding ground in the central Indian Ocean and spawning ground between southern Java and north‐western Australia were measured by laser‐ablation inductively coupled plasma mass spectrometry (LA‐ICPMS) and compared among sampling locations and developmental stages. The Na, Mg and Mn to Ca concentration ratios were significantly higher at the larval stage than at the adult stage, and the ratio reached a peak at the first inflection point of the otolith, mean ± s.d. 43·3 ± 4·9 days after hatching and decreased sharply to a low level thereafter. The temporal change of the elements:Ca ratios in the first inflection point corresponded to the life stage transition from larva to juvenile, indicating that the uptake rate of elements from ambient waters was significantly influenced by the ontogenetic change in the fish. The elemental composition at the otolith edge differed significantly in sub‐adults on the feeding grounds and adults on the spawning grounds. Thus, the otolith elemental composition can be used as a biological tracer to study the time of the ontogenetic shift and to reconstruct the past migratory environmental history of T. maccoyii . In addition, the elemental composition of the otolith core of the adult was similar between feeding and spawning grounds, indicating that the fish in the Indian Ocean had the same larval origin, which is consistent with the single spawning population hypothesis.

A Two-Step Infinite α-Cuts Fuzzy Linear Programming Method in Determination of Optimal Allocation Strategies in Agricultural Irrigation Systems - H. W. Lu; G. H. Huang; Y. P. Lin; L. He (Water Resources Management, 2009)

Nationwide surveillance of antimicrobial resistance among Haemophilus influenzae and Streptococcus pneumoniae in intensive care units in Taiwan - S.-S. Jean; P.-R. Hsueh; W.-S. Lee; H.-T. Chang; M.-Y. Chou; I.-S. Chen; J.-H. Wang; C.-F. Lin; J.-M. Shyr; W.-C. Ko; J.-J. Wu; Y.-C. Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Nationwide surveillance of antimicrobial resistance among Enterobacteriaceae in intensive care units in Taiwan - S.-S. Jean; P.-R. Hsueh; W.-S. Lee; H.-T. Chang; M.-Y. Chou; I.-S. Chen; J.-H. Wang; C.-F. Lin; J.-M. Shyr; W.-C. Ko; J.-J. Wu; Y.-C. Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Group A streptococcal infection caused by emm1 strains among children in southern Taiwan - H.-C. Lin; S.-M. Wang; Y.-L. Lin; Y.-S. Lin; J.-J. Wu; W.-J. Chuang; M. T. Lin; C.-C. Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Identification of wheat line YW243 on comprehensive resistance to several diseases by pathogens and molecular markers - H. Xie; Z. Lin; Z. Zhang; L. Du; Z. Xin; Y. Ma; X. Ye; X. Chen (Cereal Research Communications, 2008)

Cloning and infection response of tumour‐necrosis factor alpha in large yellow croaker Pseudosciaena crocea (Richardson) - F. J. Xie; Z. P. Zhang; P Lin; S. H Wang; Z. H Zou; Y. L. Wang (Journal of Fish Biology, 2008)
In this article, reverse transcriptase polymerase chain reaction (RT‐PCR) and real‐time PCR were used to clone the tumour‐necrosis factor alpha (TNF‐α) gene of the large yellow croaker Pseudosciaena crocea (Richardson) and to analyse its response to bacterial infection. The full‐length cDNA of TNF‐α contained a 5′‐untranslated region (5′‐UTR) of 68 bp, followed by an open reading frame (ORF) of 759 bp and a 3′‐UTR of 512 bp. The ORF was capable of encoding 252 amino acids with an estimated molecular mass of 28 kDa. In the 3′‐UTR, there were two putative endotoxin‐responsive motifs and five mRNA instability motifs. The deduced peptide had a transmembrane domain and a TNF‐α family signature. Multiple sequence alignments indicated that P. crocea TNF‐α shares relatively high similarity with both teleost and mammalian TNF‐α. Phylogenetic analysis showed that teleost TNF‐α was located independently in a different branch compared with mammalian TNF‐α. Real‐time PCR analysis demonstrated that the expression of TNF‐α in the head kidney of the P. crocea injected with Vibrio parahaemolyticus was most significantly higher than that of the control group at 2 and 4 days. In blood, at 2 days post‐injection, TNF‐α expression was significantly higher than that of the control group, while at 4 days post‐injection, it was most significantly higher than that of the control group.

Note: Anti-viral activity ofAilanthus altissima crude extract onRice stripe virus in rice suspension cells - J. G. Yang; Y. G. Dang; G. Y. Li; L. J. Guo; W. T. Wang; Q. W. Tan; Q. Y. Lin; Z. J. Wu; L. H. Xie (Phytoparasitica, 2008)

Yersinia enterocolitica infection in diarrheal patients - H. Zheng; Y. Sun; S. Lin; Z. Mao; B. Jiang (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Population structure and phylogeography of Aphyocypris kikuchii (Oshima) based on mitochondrial DNA variation - H.‐D. Lin; K.‐C. Hsu; K.‐T. Shao; Y.‐C. Chang; J.‐P. Wang; C.‐J. Lin; T.‐Y. Chiang (Journal of Fish Biology, 2008)
Aphyocypris kikuchii is a cyprinid species endemic to northern and eastern Taiwan and is the only primary freshwater fish native east of the Coastal Mountain Range. In total, 92 individuals of A. kikuchii from seven populations in three regions of the island were surveyed for mitochondrial DNA (mtDNA) variation. High haplotype diversity ( h = 0·989) and low nucleotide diversity ( π = 0·009) of mtDNA were detected. Negative values of Tajima’s D and unimodal mismatch distributions probably reflect a history of recent demographic expansions from small populations. Three major haplotype clusters displayed geographically non‐overlapping distributions, indicating a long‐term isolation between regions. Hierarchical analysis of molecular variance showed significant genetic structuring among populations ( Φ ST = 0·66). Significant haplotype heterogeneity was also detected among populations within regions ( Φ SC = 0·41, P Φ CT = 0·43, P c. 0·11–0·39 million years ago. Haplotypes of cluster B nested as interior nodes in the haplotype network, indicating that migrations from Shueilian (SL) populations to the northern region (cluster A) and to the eastern region (cluster C) may have occurred independently. Lineages A and B + C should be managed as two distinct evolutionarily significant units, while the northern, SL and southern groups should be managed as separate management units.

Ethmoid sinus mycology of chronic rhinosinusitis - R. S. Jiang; K. L. Liang; J. Y. Shiao; J. F. Lin; M. C. Su; C. H. Hsin; F. J. Lu (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Using FANP approach on selection of competitive priorities based on cleaner production implementation: a case study in PCB manufacturer, Taiwan - M. L. Tseng; Y. H. Lin; A. S. F. Chiu; J. C. H. Liao (Clean Technologies and Environmental Policy, 2008)

Experiences of water transfer from the agricultural to the non-agricultural sector in Taiwan - C. C. Huang; M. H. Tsai; W. T. Lin; Y. F. Ho; C. H. Tan; Y. L. Sung (Paddy and Water Environment, 2007)

Salmonellae and Campylobacters in Household and Stray Dogs in Northern Taiwan - H.-J. Tsai; H.-C. Huang; C.-M. Lin; Y.-Y. Lien; C.-H. Chou (Veterinary Research Communications, 2007)

Fracture network characteristics of a deep borehole in the Table Mountain Group (TMG), South Africa - L. Lin; H. Jia; Y. Xu (Hydrogeology Journal, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Endosperm-specific hypomethylation, and meiotic inheritance and variation of DNA methylation level and pattern in sorghum (Sorghum bicolor L.) inter-strain hybrids - M. S. Zhang; H. Y. Yan; N. Zhao; X. Y. Lin; J. S. Pang; K. Z. Xu; L. X. Liu; B. Liu (Theoretical and Applied Genetics, 2007)

Arsenic Distribution in a Tilapia (Oreochromis mossambicus) Water-Sediment Aquacultural Ecosystem in Blackfoot Disease Hyperendemic Areas - S. -W. Wang; K. -H. Lin; Y. -M. Hsueh; C. -W. Liu (Bulletin of Environmental Contamination and Toxicology, 2007)

Accumulation of additive effects generates a strong photoperiod sensitivity in the extremely late-heading rice cultivar ‘Nona Bokra’ - Y. Uga; Y. Nonoue; Z. W. Liang; H. X. Lin; S. Yamamoto; U. Yamanouchi; M. Yano (Theoretical and Applied Genetics, 2007)

A numerical study of the influence of urban expansion on monthly climate in dry autumn over the Pearl River Delta, China - W. S. Lin; C.-H. Sui; L. M. Yang; X. M. Wang; R. R. Deng; S. J. Fan; C. S. Wu; A. Y. Wang; S. K. Fong; H. Lin (Theoretical and Applied Climatology, 2007)

Apoptosis-dependent and -independent mechanisms mediate the phagocytic recognition/clearance of the HL60-A1 transfectants with prolonged survival - C.-L. Chou; L.-L. Chiang; C.-T. Yu; H.-C. Chen; K.-Y. Lee; S.-M. Lin; C.-D. Huang; W.-T. Liu; P.-C. Chou; C.-H. Wang; H.-C. Lin; H.-P. Kuo; et al. (Inflammation Research, 2007)

Mitochondrial DNA phylogeography of Glyptothorax fokiensis and Glyptothorax hainanensis in Asia - X.‐L. Chen; T.‐Y. Chiang; H.‐D. Lin; H.‐S. Zheng; K.‐T. Shao; Q. Zhang; K.‐C. Hsu (Journal of Fish Biology, 2007)
Whole mitochondrial DNA cytochrome b sequences in 62 fish from 13 locations in Southeast China identified two major clades corresponding to two allopatric taxa, Glyptothorax fokiensis fokiensis and Glyptothorax fokiensis hainanensis . Reciprocal monophyly and a molecular clock separation between these two taxa of 2·3 million years indicate these taxa should be elevated to species. Mismatch distributions and Fu’s F S statistic suggest that both G. fokiensis and G. hainanensis have experienced recent population expansions. Analysis of molecular variance indicates that most of the genetic variation resides among populations within both species, with Φ ST = 0·645 for G. fokiensis and 0·801 for G. hainanensis , suggesting restricted gene flow among populations. Significant correlations between the geographic and the genetic distances provide support for the importance of geographic isolations between populations. Nested clade analysis also confirms low levels of genetic exchanges between the two major groups and between populations within each group. The phylogeographical pattern among populations of Glyptothorax in East Asia can be attributed to historical fragmentations, demographic expansions and occasional long‐distance dispersals stimulated by tectonic activity and Ice Age climate changes.

Responses of Metapopulation Dynamics to Two Different Kinds of Habitat Destruction Caused by Human Activities - H. Y. Liu; Z. S. Lin; T. Wen (Plant Ecology, 2006)

Multifunctionality of paddy fields in Taiwan - C. C. Huang; M. H. Tsai; W. T. Lin; Y. F. Ho; C. H. Tan (Paddy and Water Environment, 2006)

Antizyme, a natural ornithine decarboxylase inhibitor, induces apoptosis of haematopoietic cells through mitochondrial membrane depolarization and caspases’ cascade - G.-Y. Liu; Y.-F. Liao; P.-C. Hsu; W.-H. Chang; M.-C. Hsieh; C.-Y. Lin; T.-C. Hour; M.-C. Kao; G. J. Tsay; H.-C. Hung (Apoptosis, 2006)

Novel polymorphic microsatellites for studying genetic diversity of red Asian arowanas - G. H. Yue; Z. Y. Zhu; G. Lin; L. C. Lo; F. Feng (Conservation Genetics, 2006)

Detection of Hong Kong 97-like H5N1 influenza viruses from eggs of Vietnamese waterfowl - Y. Li; Z. Lin; J. Shi; Q. Qi; G. Deng; Z. Li; X. Wang; G. Tian; H. Chen (Archives of Virology, 2006)

Isolation and Characterization of Two Phenol-Degrading Yeast Strains from Marine Sediment - Z. Hu; Y. R. Wu; B. K. Lin; K. Maskaoui; D. H. Zhuang; T. L. Zheng (Bulletin of Environmental Contamination and Toxicology, 2006)

Potential Volatile Organic Compound Exposure from Dry Process Photocopiers in Operation-Idle Mode - D.-J. Hsu; H.-L. Huang; H.-Y. Lin; T.-S. Lin (Bulletin of Environmental Contamination and Toxicology, 2006)

Enhanced viability of a nervous necrosis virus‐infected stable cell line over‐expressing a fusion product of the zfBcl‐x L and green fluorescent protein genes - S‐P Chen; H‐L Yang; H‐Y Lin; M‐C Chen; J‐L Wu; J‐R Hong (Journal of Fish Diseases, 2006)
Nervous necrosis virus (NNV) infection induces host cell apoptosis by an ill‐understood process. We utilized a fusion between enhanced green fluorescent protein (EGFP) and the zfBcl‐x L gene in GL‐av cells to select for zfBcl‐x L stable cell lines and to assess the effectiveness of the anti‐apoptotic protein Bcl‐x L in circumventing NNV‐induced cell death. Stable EGFP and EGFP‐Bcl‐x L ‐expressing clones were obtained at high purity within 2.5–3 months. In the latter, the EGFP‐Bcl‐x L fusion protein (approximately 58.2 kDa, as ascertained by Western blot) was predominantly targeted to mitochondria. We assayed for apoptosis in red‐spotted grouper NNV Tainan no. 1 (RGNNV TN1)‐infected cells with terminal deoxynucleotidyl transferase (TdT)‐mediated end labelling (TUNEL) of DNA at different virus doses. NNV infection of NNV Bcl‐x L GL‐av cell line revealed a protective effect, with a decrease in TUNEL‐positive cells of 7%, 8% and 31.8% at 24, 48 and 72 h, respectively. In addition, RGNNV infection of the Bcl‐x L GL‐av cell line revealed a protective effect, with an enhanced viability of 3%, 40% and 73% at 24, 48, and 72 h, respectively. We conclude that NNV‐induced apoptotic cell death can be lessened in transgenic grouper fish cells.

Ancient paddy soils from the Neolithic age in China’s Yangtze River Delta - Z. H. Cao; J. L. Ding; Z. Y. Hu; H. Knicker; I. Kögel-Knabner; L. Z. Yang; R. Yin; X. G. Lin; Y. H. Dong (The Science of Nature, 2006)

Renoprotective effects of combination of angiotensin converting enzyme inhibitor with mycophenolate mofetil in diabetic rats - Y. -G. Wu; H. Lin; H Qian; M. Zhao; X. -M. Qi; G. -Z. Wu; S. -T. Lin (Inflammation Research, 2006)

Detection and characterisation of a second potyvirus from Thunberg fritillary in China - J. Chen; H.-Y. Zheng; Y.-H. Shi; M. J. Adams; C.-B. Wei; L. Lin; J.-P. Chen (Archives of Virology, 2006)

Protoplast electrofusion between common wheat (Triticum aestivum L.) and Italian ryegrass (Lolium multiflorum Lam.) and regeneration of mature cybrids - T. M. Ge; X. H. Lin; F. L. Qin; S. W. Yu; Y. J. Yu (In Vitro Cellular & Developmental Biology - Plant, 2006)

The Complete Mitochondrial Genome Sequence and Characterization of Single-Nucleotide Polymorphisms in the Control Region of the Asian Seabass (Lates calcarifer) - G. Lin; L. C. Lo; Z. Y. Zhu; F. Feng; R. Chou; G. H. Yue (Marine Biotechnology, 2006)

Nucleotide sequence and mRNA expression analysis of β-actin gene in the orange-spotted grouper Epinephelus coioides - W. M. Zhang; Y. Zhang; L. H. Zhang; S. G. Wang; T. Y. Zhu; D. Lin; G. Z. Ma (Fish Physiology and Biochemistry, 2005)

Characterisation of the welsh onion isolate of Shallot yellow stripe virus from China - J. Chen; C.-B. Wei; H.-Y. Zheng; Y.-H. Shi; M. J. Adams; L. Lin; Q.-Y. Zhang; S.-J. Wang; J.-P. Chen (Archives of Virology, 2005)

Risk Assessment of Arsenic Exposure from Consumption of Cultured Milkfish, Chanos chanos (Forsskål), from the Arsenic-Contaminated Area in Southwestern Taiwan - M.-C. Lin; H.-Y. Lin; H.-H. Cheng; Y.-C. Chen; C.-M. Liao; K.-T. Shao (Bulletin of Environmental Contamination and Toxicology, 2005)

Isolation and characterization of actinomycetes antagonistic to pathogenic Vibrio spp. from nearshore marine sediments - J. L. You; L. X. Cao; G. F. Liu; S. N. Zhou; H. M. Tan; Y. C. Lin (World Journal of Microbiology and Biotechnology, 2005)

A new potyvirus from Thunberg fritillary (Fritillaria thunbergii Miq.) in Zhejiang, China - C.-B. Wei; J. Chen; Q.-Y. Zhang; Y.-H. Shi; L. Lin; H.-Y. Zheng; M. J. Adams; J.-P. Chen (Archives of Virology, 2005)

Phylogenetic analysis of classical swine fever virus in Taiwan - C. H. Pan; M. H. Jong; T. S. Huang; H. F. Liu; S. Y. Lin; S. S. Lai (Archives of Virology, 2005)

Etoposide (VP-16) sensitizes p53-deficient human non-small cell lung cancer cells to caspase-7-mediated apoptosis - C.-C. Chiu; C.-H. M. Y. Lin; K. Fang (Apoptosis, 2005)

Orographic effects on a conditionally unstable flow over an idealized three-dimensional mesoscale mountain - S.-H. Chen; Y.-L. Lin (Meteorology and Atmospheric Physics, 2005)

Histology and histochemical enzyme‐staining patterns of major immune organs in Epinephelus malabaricus - H.‐T. Lin; H.‐Y. Lin; H.‐L. Yang (Journal of Fish Biology, 2005)
The histological architecture of major immune organs in the Malabar grouper Epinephelus malabaricus was investigated. The novel characteristics such as melanomacrophage centres (MMCs) appeared in the thymus and lymphopoietic tissue formed as foci in the head kidney. Leukocyte distribution in organs was identified by enzyme histochemistry. β‐glucuronidase (BG) reactive cells in the cortex region of the thymus were botryoidally aggregated. Both acid phosphatase (AcP) and BG reactive cells concentrated within the specialized lymphopoietic foci in the head kidney, suggesting that the foci might be functional. Primitive histological characters of immunity were observed in the spleen. Although leukocyte aggregation was demonstrated in the spleen, additional enzyme histochemistry indicated that the aggregate might not be the equivalent of white pulp found in other vertebrates. The histological evidence did not support intestinal involvement in the immune system: there was no demonstrable gut associated lymphoid tissue. The limited distribution in the cortex and medulla boundary and the condensed format of the lymphocytes suggests a functional role for the MMC in the thymus of E. malabaricus . The MMC appearance in the thymus of a teleost was unusual.

Manganese Uptake and Accumulation by Two Populations of Phytolacca acinosa Roxb. (Phytolaccaceae) - S. G. Xue; Y. X. CHEN; A. J. M. Baker; R. D. Reeves; X. H. Xu; Q. Lin (Water, Air, & Soil Pollution, 2005)

Further molecular characterisation of potyviruses infecting aroid plants for medicinal use in China - Y.-H. Shi; X.-Y. Hong; J. Chen; M. J. Adams; H.-Y. Zheng; L. Lin; B.-X. Qin; J.-P. Chen (Archives of Virology, 2005)

Fisheries of two tropical lagoons in Ghana, West Africa - H. R. Dankwa; J. M. Shenker; J. Lin; P. K. Ofori‐Danson; Y. Ntiamoa‐Baidu (Fisheries Management and Ecology, 2004)
The fisheries of two coastal lagoons, Keta and Songor, were studied as part of Ghana Coastal Wetlands Management Project (GCWMP) aimed at sustainable exploitation of wetland resources. Fish samples were obtained with seine nets and cast net as well as from local fishermen. Water quality parameters (pH, dissolved oxygen, temperature and turbidity) were similar in the two lagoons, except for salinity, which was significantly different ( P Sarotherodon melanotheron Rüppell, and the redchin tilapia, Tilapia guineensis (Bleeker), being the most important commercial fishes in both lagoons. The number of individuals for each species in Songor Lagoon were far more abundant, with densities several orders of magnitude higher than in Keta Lagoon. However, both species were significantly larger ( P S. melanotheron and T. guineensis respectively. Over‐fishing, use of small‐size mesh nets, limited mixing of marine and fresh water were some of the factors limiting fish production in both lagoons.

Identification of a 98-kb DNA segment containing the rice Eui gene controlling uppermost internode elongation, and construction of a TAC transgene sublibrary - Y.-H. Xu; Y.-Y. Zhu; H.-C. Zhou; Q. Li; Z.-X. Sun; Y.-G. Liu; H.-X. Lin; Z.-H. He (Molecular Genetics and Genomics, 2004)

Acute Aquatic Toxicity of N-Methyl-2-Pyrrolidinone to Daphnia magna - C.-H. Lan; C.-Y. Peng; T.-S. Lin (Bulletin of Environmental Contamination and Toxicology, 2004)

A new potyvirus from tuberose ( Polianthes tuberosa ) in China - L. Lin; H.-Y. Zheng; J. Chen; J.-P. Chen; Q.-Y. Zhang; M.-F. Zhao; J. F. Antoniw; M. J. Adams (Archives of Virology, 2004)

Natural frequency assessment of stability of root keeper magnetic devices - H. -M. Huang; D. -Z. Liu; Y. -Y. Shiau; C. -Y. Yeh; C. -T. Lin; S. -Y. Lee (Medical & Biological Engineering & Computing, 2004)

Adaptive processing bandwidth adjustment for laser Doppler flowmetry - Y. Y. Chen; Y. H. Lin; I. C. Jan; R. S. Liu; N. K. Chou; G. -J. Jan (Medical & Biological Engineering & Computing, 2004)

Biological functions of the cytoplasmic TGBp1 inclusions of bamboo mosaic potexvirus - H.-T. Hsu; Y.-H. Hsu; I.-P. Bi; N.-S. Lin; B.-Y. Chang (Archives of Virology, 2004)

Predicted ATP-binding cassette systems in the phytopathogenic mollicute Spiroplasma kunkelii - Y. Zhao; H. Wang; R. W. Hammond; R. Jomantiene; Q. Liu; S. Lin; B. A. Roe; R. E. Davis (Molecular Genetics and Genomics, 2004)

Kinetic Studies on the Effects of Organophosphorus Pesticides on the Growth of Microcystis aeruginosa and Uptake of the Phosphorus Forms - P.-J. Zhou; H. Shen; J. Lin; L.-R. Song; Y.-D. Liu; Z.-B. Wu (Bulletin of Environmental Contamination and Toxicology, 2004)

Kinetic Studies on the Combined Effects of Lanthanum and Cerium on the Growth of Microcystis aeruginosa and their Accumulation by M. aeruginosa - P.-J. Zhou; J. Lin; H. Shen; T. Li; L.-R. Song; Y.-W. Shen; Y.-D. Liu (Bulletin of Environmental Contamination and Toxicology, 2004)

Mapping of quantitative trait loci controlling low-temperature germinability in rice (Oryza sativa L.) - K. Fujino; H. Sekiguchi; T. Sato; H. Kiuchi; Y. Nonoue; Y. Takeuchi; T. Ando; S. Y. Lin; M. Yano (Theoretical and Applied Genetics, 2004)

Pilot point temperature regulation for thermal lesion control during ultrasound thermal therapy - H. -L. Liu; Y. -Y. Chen; J. -Y. Yen; W. -L. Lin (Medical & Biological Engineering & Computing, 2004)

Detection and classification of allexiviruses from garlic in China - J. Chen; H.-Y. Zheng; J. F. Antoniw; M. J. Adams; J.-P. Chen; L. Lin (Archives of Virology, 2004)

Arsenic Accumulation and Acute Toxicity in Aquacultural Juvenile Milkfish ( Chanos chanos ) from Blackfoot Disease Area in Taiwan - M.-C. Lin; H.-H. Cheng; H.-Y. Lin; Y.-C. Chen; Y.-P. Chen; G.-P. Chang-Chien; Y.-H. Chou; C.-M. Liao; C.-F. Dai; B.-C. Han; C.-W. Liu (Bulletin of Environmental Contamination and Toxicology, 2004)

A virus related to Soybean mosaic virus from Pinellia ternata in China and its comparison with local soybean SMV isolates - J. Chen; H.-Y. Zheng; L. Lin; M. J. Adams; J. F. Antoniw; M.-F. Zhao; Y.-F. Shang; J.-P. Chen (Archives of Virology, 2004)

QTLs for Na+ and K+ uptake of the shoots and roots controlling rice salt tolerance - H. X. Lin; M. Z. Zhu; M. Yano; J. P. Gao; Z. W. Liang; W. A. Su; X. H. Hu; Z. H. Ren; D. Y. Chao (Theoretical and Applied Genetics, 2004)

Occurrence and sequences of Lily mottle virus and Lily symptomless virus in plants grown from imported bulbs in Zhejiang province, China - H.-Y. Zheng; J. Chen; M.-F. Zhao; L. Lin; J.-P. Chen; J. F. Antoniw; M. J. Adams (Archives of Virology, 2003)

Gene content and organization of an 85-kb DNA segment from the genome of the phytopathogenic mollicute Spiroplasma kunkelii - Y. Zhao; R. W. Hammond; R. Jomantiene; E. L. Dally; I.-M. Lee; H. Jia; H. Wu; S. Lin; P. Zhang; S. Kenton; F. Z. Najar; A. Hua; et al. (Molecular Genetics and Genomics, 2003)

Detection ofBurkholderia pseudomallei in rice fields with PCR-based technique - C. M. Kao; S. C. Chen; Y. S. Chen; H. M. Lin; Y. L. Chen (Folia Microbiologica, 2003)

Polychlorinated Biphenyls in Taiwanese Primipara Human Milk and Associated Factors - H.-R. Chao; S.-L. Wang; L.-Y. Lin; H.-Y. Yu; Y.-K. Lu; W.-L. Chou; Y.-L. Guo; L. W. Chang (Bulletin of Environmental Contamination and Toxicology, 2003)

Human infection by a swine influenza A (H1N1) virus in Switzerland - V. Gregory; M. Bennett; Y. Thomas; L. Kaiser; W. Wunderli; H. Matter; A. Hay; Y. P. Lin (Archives of Virology, 2003)

Hibiscus protocatechuic acid inhibits lipopolysaccharide-induced rat hepatic damage - Lin W.-L.; Hsieh Y.-J.; Chou F.-P.; Wang C.-J.; Cheng M.-T.; Tseng T.-H. (Archives of Toxicology, 2003)

Establishment of cell lines from a tropical grouper, Epinephelus awoara (Temminck & Schlegel), and their susceptibility to grouper irido‐ and nodaviruses - Y‐S Lai; J A C John; C‐H Lin; I‐C Guo; S‐C Chen; K Fang; C‐H Lin; C‐Y Chang (Journal of Fish Diseases, 2003)
Four tropical marine fish cell lines have been established from the eye, fin, heart and swim bladder of grouper, Epinephelus awoara (Temminck & Schlegel). Optimum media and temperature conditions for maximum growth were standardized. The eye and swim bladder cells were mostly epithelial, but the fin and heart cells were mostly fibroblastic. The viability of cells was 95% after 1 year of storage in liquid nitrogen (−196 °C). Besides these four cell lines, previously established grouper brain, kidney and liver cell lines were also used for a viral susceptibility study which showed that all the cell lines were sensitive to grouper iridovirus, whereas only brain, fin and liver cell lines were susceptible to the yellow grouper nervous necrosis virus (a nodavirus). Electron microscopy studies of the grouper irido‐ and nodaviruses in ultrathin sections of infected cells showed an abundance of viral particles in the cytoplasm of the virus‐infected cells indicating the effective replication of these two viruses. It is suggested that these cell lines can be used for the isolation of putative fish specific viruses and provide a valuable tool to study the mechanisms of host–pathogen interactions. Furthermore, these cell lines upon transfection, using pEGFP‐C1 and pEGFP‐aMT 2.5 (ayu metallothionein promoter), produced significant fluorescent signals indicating their utility for exogenous studies.

Lactococcus garvieae , a cause of disease in grey mullet, Mugil cephalus L., in Taiwan - S‐C Chen; L‐L Liaw; H‐Y Su; S‐C Ko; C‐Y Wu; H‐C Chaung; Y‐H Tsai; K‐L Yang; Y‐C Chen; T‐H Chen; G‐R Lin; S‐Y Cheng; et al. (Journal of Fish Diseases, 2002)

Specific detection ofPythium aphanidermatum from hydroponic nutrient solution by booster PCR with DNA primers developed from mitochondrial DNA - P. H. Wang; L. M. Boo; Y. S. Lin; Y. Yeh (Phytoparasitica, 2002)

Residential Water Supply as a Likely Cause of Community-Acquired Legionnaires' Disease in an Immunocompromised Host - Chen Y-S.; Lin W-R.; Liu Y-C.; Chang C-L.; Gan V-L.; Huang W-K.; Huang T-S.; Wann S-R.; Lin H-H.; Lee S.; Huang C-K.; Chin C.; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

Modulation of calcium balance in tilapia larvae ( Oreochromis mossambicus ) acclimated to low-calcium environments - Chou M.-Y.; Lu F.-I.; Lin H.-C.; Hwang P.-P.; Yang C.-H. (Journal of Comparative Physiology B, 2002)

A genetic linkage map of Nicotiana plumbaginifolia/ Nicotiana longiflora based on RFLP and RAPD markers - T. Y. Lin; Y. Y. Kao; S. Lin; R. F. Lin; C. M. Chen; C. H. Huang; C. K. Wang; Y. Z. Lin; C. C. Chen (Theoretical and Applied Genetics, 2001)

Plasmids carrying cloned fragments of RF DNA from the filamentous phage φLf can be integrated into the host chromosome via site-specific integration and homologous recombination - N.-T. Lin; R.-Y. Chang; S.-J. Lee; Y.-H. Tseng (Molecular Genetics and Genomics, 2001)

Propagation of yellow grouper nervous necrosis virus (YGNNV) in a new nodavirus‐susceptible cell line from yellow grouper, Epinephelus awoara (Temminck & Schlegel), brain tissue - Y‐S Lai; S Murali; H‐C Chiu; H‐Y Ju; Y‐S Lin; S‐C Chen; I‐C Guo; K Fang; C‐Y Chang (Journal of Fish Diseases, 2001)
A nodavirus was isolated from diseased yellow grouper, Epinephelus awoara , larvae cultured in southern Taiwan. The histopathology and RT–PCR results confirmed that it was a fish nodavirus; its coat protein gene sequence was similar to that of red spotted grouper nervous necrosis virus (RGNNV) and it is named yellow grouper nervous necrosis virus (YGNNV). A new nodavirus‐susceptible cell line, grouper brain (GB) was established and characterized from the brain tissue of yellow grouper. The GB cells multiplied well in Leibovitz’s L‐15 medium supplemented with 10% foetal bovine serum at temperatures between 24 and 32 °C, and have been subcultured more than 80 times, becoming a continuous cell line. The GB cell line consists of fibroblast‐like cells and some epithelioid cells. The cell line yielded titres of YGNNV up to 10 8.5 TCID 50 mL –1 . The GB cells effectively replicated the virus at 28 °C, which could be purified to homogeneity by caesium chloride gradient centrifugation. Electron microscopy studies showed that purified virus particles were 25–30 nm in diameter. The cytoplasm of infected cells was filled with aggregates of virus particles. These results indicate that the GB cell line is a significant tool for the study of fish nodaviruses.

Molecular epidemiology of enterovirus 71 in Taiwan - P.-Y. Chu; K.-H. Lin; K.-P. Hwang; L.-C. Chou; C.-F. Wang; S.-R. Shih; J.-R. Wang; Y. Shimada; H. Ishiko (Archives of Virology, 2001)

Blood and Urine Cadmium Levels in Relation to Demographic and Life Style in Middle Aged and Elderly Men - Y. C. Chen; Y. S. Pu; R. S. Lin; C. Y. Yang; M. K. Lai; S. H. Liu; F.-C. Sung (Bulletin of Environmental Contamination and Toxicology, 2001)

Compression studies of gibbsite and its high-pressure polymorph - E. Huang; J.-F. Lin; J. Xu; T. Huang; Y.-C. Jean; H.-S. Sheu (Physics and Chemistry of Minerals, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

A SINE species from hippopotamus and its distribution among animal species - O. Nomura *, , Z.-H. Lin; Not Available Not Available; Y. Wada; H. Yasue (Mammalian Genome, 1998)

Analysis of QTL×environment interaction for yield components and plant height in rice - J.-Y. Zhuang; H.-X. Lin; J. Lu; H.-R. Qian; S. Hittalmani; N. Huang; K.-L. Zheng (Theoretical and Applied Genetics, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Phylogenetic analysis of feline immunodeficiency virus isolated from cats in Taiwan - G. Inada; T. Miyazawa; Y. Inoshima; M. Kohmoto; Y. Ikeda; C. -H. Liu; J. A. Lin; T. -F. Kou; T. Mikami (Archives of Virology, 1997)

Human T-lymphotropic Virus Type II Infection inVietnamese Thalassemic Patients - M. T. Lin; B. T. Nguyen; T. V. Binh; T. V. Be; T. Y. Chiang; L. H. Tseng; Y. C. Yang; K. H. Lin; Y. -C. Chen (Archives of Virology, 1997)

Physical mapping of four RAPDs in the B chromosome of maize - B.-Y. Lin; H.-P. Chou (Theoretical and Applied Genetics, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Identifying different types of de-differentiated microspores from indica-japonica F1 hybrids with subspecies-differentiating RFLP probes in rice - J. -H. Xie; M. -W. Gao; J. Lu; J. -Y. Zhuang; H. -X. Lin; H. -R. Qian; K. -L. Zheng (Theoretical and Applied Genetics, 1997)

Lipid peroxidation in rats administrated with mercuric chloride - Y. L. Huang; S. L. Cheng; T. H. Lin (Biological Trace Element Research, 1996)

Capsid protein of cucumber mosaic virus accumulates in the nuclei and at the periphery of the nucleoli in infected cells - N. -S. Lin; C. -E. Hsieh; Y. -H. Hsu (Archives of Virology, 1996)

N-Nitroso-N-(3-keto-1,2-butanediol)-3′-nitrotyramine - C. -J. Wang; H. -P. Huang; T. -H. Tseng; Y. -L. Lin; S. -J. Shiow (Archives of Toxicology, 1995)

Complete genomic RNA sequences of cucumber mosaic virus strain NT9 from Taiwan - Y. -H. Hsu; C. -W. Wu; B. -Y. Lin; H. -Y. Chen; M. -F. Lee; C. -H. Tsai (Archives of Virology, 1995)

A long lytic cycle in filamentous phage Cf1tv infectingXanthomonas campestris pv.citri - T. -T. Kuo; C. -C. Chiang; S. -Y. Chen; J. -H. Lin; J. -L. Kuo (Archives of Virology, 1994)

The skin, tongue, and brain as favorable organs for hog cholera diagnosis by immunofluorescence - I. C. Pan; T. S. Huang; C. H. Pan; Shenq-Yi Chern; Shu-Hwae Lee; Y. L. Lin; B. Y. Huang; C. C. Lin; N. J. Li; J. P. Lin; Y. H. Yang; S. Y. Chiu; et al. (Archives of Virology, 1993)

Evolutionary study on the coxsackievirus A 24 variant causing acute hemorrhagic conjunctivitis by oligonucleotide mapping analysis of RNA genome - K. Miyamura; N. Takeda; M. Tanimura; T. Ogino; S. Yamazaki; C. -W. Chen; K. -H. Lin; S. Y. Lin; A. Ghafoor; M. Yin-Murphy (Archives of Virology, 1990)